Место снов: [роман] / Эдуард Веркин - Веркин Эдуард (Хроника Страны Мечты, 2006)
Экземпляры: (20181010) / Инвентарный номер: 33314 / Цена: 162.03 / Сис.шифр: Р2 / Авт.знак: В 31 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6